Implantación de la contabilidad comercial mediante el sistema de cuenta permanente para el micromercado La Economía, del cantón Catamayo, provincia de Loja, periodo julio a septiembre - 2014 - Celi Celi, Ana Gabriela (2015)
This paper titled "IMPLEMENTATION OF COMMERCIAL ACCOUNTING THROUGH THE SYSTEM OF PERMANENT ACCOUNT FOR MICROMARKET THE ECONOMY, THE CANTON CATAMAYO, PROVINCE OF LOJA, PERIOD JULY TO SEPTEMBER - 2014", he performed it as a prerequisite to obtaining the title of Engineer in Accounting and Auditing, CPA. Additional to the implementation of the Business accounting would be bringing with Mr. Fredi Lidiberto Celi Riofrío, to give an accounting tool that serves to registration and real control of economic activities and financial you have in your business, whose results will allow its owner manager make decisions for optimal growth of the same. For the implementation of commercial accounting was raised previously objectives which were met in full; was mainly fulfilled developing a plan and a manual analysis, the lifting of an inventory, registration of economic activities in the general journal, and the preparation of financial statements respective unveiled economic situation the company under study during the period July to September 2014. After the execution of the business accounting process in micromarket Economics, could determine net income for the year, which will allow owners of the company have a clear vision of their business and importance of implementing the commercial accounting; It is recommended to continue recording the accounting process as it will provide the reasonable and timely decisions to Financial Statements